The impact of Vitamin D on Muscle Metabolism, Bioenergetic Responses and Exercise Performance - Romeu Montenegro, Karina (Curtin University, 2021)
This PhD thesis describes the effects of Vitamin D on skeletal muscle and includes details of two main research projects. The first study validated a physiologically significant effect of VitD3 in proliferation, differentiation, protein synthesis and mitochondrial metabolism in primary human skeletal muscle cells, in cell culture. The second study demonstrated that VitD3 supplementation does not result in additional benefits on muscle strength, power, resting metabolic rate and body composition in VitD sufficient physically active adults.